2009
DOI: 10.1007/s10867-009-9167-7
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed-laser creation and characterization of giant plasma membrane vesicles from cells

Abstract: Femtosecond-pulsed laser irradiation was found to initiate giant plasma membrane vesicle (GPMV) formation on individual cells. Laser-induced GPMV formation resulted from intracellular cavitation and did not require the addition of chemical stressors to the cellular environment. The viscosity, structure, and contents of laser-induced GPMVs Electronic supplementary material The online version of this article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 45 publications
(55 reference statements)
3
11
0
Order By: Relevance
“…Large plasma membrane vesicles, or blebs, are clearly noticeable in Figure 3a, and to a lesser extent in Figure 3c and e, indicating the rupture of the cellular plasma membrane–cytoskeleton interface due to the combined effect of the pulse irradiation and the nanoparticles. Similar vesicles were previously observed in cells as a result of tightly focused femtosecond pulse beam irradiation 13, 25…”
Section: Resultssupporting
confidence: 80%
“…Large plasma membrane vesicles, or blebs, are clearly noticeable in Figure 3a, and to a lesser extent in Figure 3c and e, indicating the rupture of the cellular plasma membrane–cytoskeleton interface due to the combined effect of the pulse irradiation and the nanoparticles. Similar vesicles were previously observed in cells as a result of tightly focused femtosecond pulse beam irradiation 13, 25…”
Section: Resultssupporting
confidence: 80%
“…Indeed, interfering with the activities of linking molecules such as ezrin / radixin / moesin (ERM) and class I myosins frequently induced blebbing in zebrafish prechordal plate mesendoderm progenitor cells [ 35 ]. Local pulsed-laser-induced ablation of the cell membrane can induce blebbing [ 36 , 37 ], which also supports the above idea. In the present study, virtually no blebs were observed in the anucleate fragments of myosin II-null cells; instead, very small extensions were often observed.…”
Section: Discussionsupporting
confidence: 56%
“…[57]) or in some fully-differentiated cells (e.g., inner hair cells [58], skeletal muscle fibers [33]). Once formed, these balloon blebs are typically not retrieved.…”
Section: Discussionmentioning
confidence: 99%